2018
DOI: 10.1186/s12974-018-1344-9
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral myeloid cells contribute to brain injury in male neonatal mice

Abstract: BackgroundNeonatal brain injury is increasingly understood to be linked to inflammatory processes that involve specialised CNS and peripheral immune interactions. However, the role of peripheral myeloid cells in neonatal hypoxic-ischemic (HI) brain injury remains to be fully investigated.MethodsWe employed the Lys-EGFP-ki mouse that allows enhanced green fluorescent protein (EGFP)-positive mature myeloid cells of peripheral origin to be easily identified in the CNS. Using both flow cytometry and confocal micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(56 citation statements)
references
References 69 publications
2
54
0
Order By: Relevance
“…Evidence from studies examining PBMCs isolated from adult humans suggests that sex differences in stimulated PBMC properties and secretion exist ( 105 107 ). While sex differences in secretion of PBMCs isolated at neonatal time points are not well-defined ( 35 , 37 ), evidence exists demonstrating sex-specific differences in brain inflammation following circulating myeloid cells depletion in neonatal mice ( 108 ) and that inflammatory responses following immune cell activation in the immature brain differ between males and females, as reviewed by Mallard et al ( 109 ). Thus, separate pooling of males and female peripheral blood from P7 pups for sex-specific analysis represents an important future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence from studies examining PBMCs isolated from adult humans suggests that sex differences in stimulated PBMC properties and secretion exist ( 105 107 ). While sex differences in secretion of PBMCs isolated at neonatal time points are not well-defined ( 35 , 37 ), evidence exists demonstrating sex-specific differences in brain inflammation following circulating myeloid cells depletion in neonatal mice ( 108 ) and that inflammatory responses following immune cell activation in the immature brain differ between males and females, as reviewed by Mallard et al ( 109 ). Thus, separate pooling of males and female peripheral blood from P7 pups for sex-specific analysis represents an important future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Leukocyte migration to the CNS is a hallmark of many neurological diseases including neonatal encephalopathy (Smith et al, 2018). Leukocyte accumulation in CSF and subarachnoid spaces is also observed in some CNS pathologies, most markedly in meningitis (Wilson et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, to microglia, macrophages are plastic in phenotype and can either exacerbate brain injury or promote regeneration. There is evidence that monocytes are recruited into the brain after HI as levels of monocyte chemoattractant protein-1 (MCP-1) increase acutely within the brain and in mouse models in which only mature myeloid cells from the periphery express an enhanced green fluorescent protein, fluorescence is detected 24 h and seven days after HI within the CNS [ 102 , 103 ]. In the same model, antibody-mediated depletion of monocytes was neuroprotective but only in male mice.…”
Section: Preterm Brain Injury—timing Is Keymentioning
confidence: 99%
“…In the same model, antibody-mediated depletion of monocytes was neuroprotective but only in male mice. This suggests monocytes contribute to brain damage in male mice [ 102 ]. Contrarily, it has been shown that mice pre-conditioned with LPS generated splenic monocytes that protect the brain in a stroke model [ 104 ].…”
Section: Preterm Brain Injury—timing Is Keymentioning
confidence: 99%